The Knowledge Economy and Education and Training in South Asia - Riboud, Michelle; Savchenko, Yevgeniya; Tan, Hong (World Bank, Washington, DC, 2014)
How education and training systems respond to the sweeping changes brought about by globalization and the knowledge economy can have far-reaching implications for developing countries in terms of sustainability of growth, competitiveness, job creation, and poverty reduction. This issue is especially pertinent to the countries of South Asia, which are currently growing at a rapid pace and are gradually becoming more integrated into the world economy. This regional study is a first attempt to address these questions. Its main objective is to document and compare trends in education and training in the countries of South Asia, as well as the associated changes in earnings and employment. It draws upon household, labor force, and firm-level surveys from 1990 to the most recent year available. The analysis focuses on Bangladesh, India, Pakistan, and Sri Lanka (countries with well-developed surveys), with some references to Bhutan, the Maldives, and Nepal, along with comparisons with countries in East Asia and with other regions.